How education changes clinical documentation in early pregnancy. (18th May 2016) - Ali, Fida; Higgins, Mary F.
Abstract : The aim of this audit was to record medical history taking in the records of women attending with early pregnancy issues in order to assess the effect of training in this area. The medical education intervention comprised of a 30-min interactive tutorial. Retrospective chart review at three time points: pre education (July 2013, n = 45), immediately post-education (August 2013, n = 45) and longer term post-intervention (October 2013, n = 20). Pre-education, medical history was missing in 77.8% of charts compared to 13.4% immediately post-intervention and 10% long-term post-intervention ( p < 0.05). Similar findings were noted with regard to documentation of age, surgical history, medications, allergies and last menstrual period (LMP). While there was a high rate of ultrasound investigations, the documentation of these (by placing an image in the chart) improved after the intervention. Education in requirements for medical history taking can improve documentation.